Editorial - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Jacó Vilela, Ana Maria; Mendes, Deise Maria Fernandes; Quadros, Laura Cristina de Toledo; Valentim, Renata Patrícia Forain de; Darriba, Vinicius Anciães (Estudos e Pesquisas em Psicologia, 2018)
Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Ana Maria Jacó Vilela, Deise Maria Fernandes Mendes, Laura Cristina de Toledo Quadros, Renata Patrícia Forain de Valentim, Vinicius Anciães Darriba